PENGUATAN MANAJEMEN BIMBINGAN DAN KONSELING DI SD MELALUI KELOMPOK KERJA KEPALA SEKOLAH KECAMATAN KEDIRI - Juliawan Wayan; Ni Wayan Suastini; Ni Komang Sri Yuliastini; I Wayan Susanta; I Nyoman Rajeg Mulyawan; Roro Dwi Umi Badriah (Sewagati, 2026)
This community service activity was initiated in response to the need for elementary school teachers in Kediri District to improve their competencies in guidance and counseling management. In addition, teachers also require basic skills in conducting needs assessments, particularly to support services for children with special needs in schools. Enhancing competencies in guidance and counseling management is expected to support the development of more comprehensive and inclusive educational services for all students. The activity was carried out through three main stages: planning, implementation, and evaluation. During the planning stage, the service team conducted coordination meetings to ensure the activity was well prepared. In the implementation stage, training sessions were conducted involving elementary school teachers and principals. Meanwhile, the evaluation stage was carried out through interviews and the distribution of Google Forms to participants. The results of the activity showed that all participants were highly enthusiastic throughout the training. Participants were also able to understand the materials and improve their skills in providing services for children with special needs effectively.